Pengaruh Kadar Sulfur Dan Plastisizer Paraffin Terhadap Morfologi Dan Sifat Karet Alam Thermoset Dengan Filler Abu Sawit/Carbon Black - Maradona Maradona; Nirwana Nirwana; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Sulfur and plasticizer has an important role in the manufacture of thermoset rubber. Plasticizer serves to increase the spread of filler in the elastic properties of rubber. While the function of sulfur during the vulcanization process. This research aims to study the effect of sulfur and paraffin plasticizers on the morphology and properties of thermoset rubber with palm ash /carbon black as filler. sufur content used were 1,5 phr 2,5 phr and 3 phr (per hundred rubber ). Plastisizer content used were 2,5 phr and 5 phr. Mastication process is carried out using a roll mill at room temperature, roll rotational speed of 20 rpm, and the overall time of the manufacture of compound ± 50 minutes. Activator used was ZnO, a co–activator used was stearic acid, an accelerator used was MBTS, antidegradant used was TMQ. Vulcanization process was carried out at a temperature of 150 °C and pressure of 50 kgf/cm2. Testing of mechanical properties includes tensile strength, elongation at break and elastic modulus using standard ISO 527-2 type 5A with a universal testing machine. Testing morphology was carried out using a scanning electron microscope (SEM). Other parameter tested is water absorption resistance. The results showed that the rate of sulfur and plasticizer influence the properties of vulcanized rubber. The best mechanical properties obtained at 2.5 phr sulfur and 2.5 phr plasticizer with filler ratio of palm ash /carbon black 30/70 with a tensile strength of 18.41 MPa, elongation at break 1155.9 % and elastic modulus of 0.9 MPa.                                     Keywords : sulfur , plasticizers , fillers hybrid , natural rubber , vulcanized